LAYANAN BIMBINGAN KELOMPOK SECARA DARING MELALUI TEKNIK MODELING UNTUK KEPERCAYAAN DIRI SISWA SMA KELAS XI DI SMAN 1 GUNUNGHALU - Periana Farihah; Wahyu Hidayat; Tuti Alawiyah (IKIP Siliwangi, 2023)
The purpose of this study was to determine the offer of online group counseling on the self-esteem of class XI students at SMA Negeri 1 Gununghalu. The design of this study used descriptive qualitative research methids. The subjects of this study were six students of class XI SMA Negeri 1 Gununghalu. This survey tool uses observation guides, interview guides, surveys, and documentation. Data analysis technigues used are data reduction, dan display, and data inference. The results obtained from the survey are changes in students’ self-confidence after beibg given online group counseling services through modeling technology. One of the obstacles faced by BK teachers when implementing online group counseling services through modeling technology is the difficulty connectivity and networks. The results showed that online group counseling services can help bulid self-confidence through self-confidence modeling techniques of students.Keywords: Group Guidance, Modeling Techniques, self-Confidence